English for Specific Purposes: Selected Readings from the Field of English for Criminal Justice and Security - Kompara Lukančič , Mojca (University of Maribor Press, 2023)
The scientific monograph deals with the field of the language for specific purposes for the field of criminal justice and security, and consists of two parts. The first part is more theoretically based and it focuses on language concepts, language acquisition, the language for specific purposes and English as for specific purposes and "lingua franca”, the development of terminology, and the position of terminology in criminal justice and security studies. In the second part, which is more applied, the focus is on language resources and dictionaries for criminal justice and security, the portals Fran and Slovarji.si are presented as well as reference dictionaries for the fields of security, police, law and the military. In the second part, we also find an outline of the English-Slovenian dictionary of abbreviations for the field of criminal justice and security and the English-Slovene dictionary of collocations in the field of criminal justice and security, as well as an overview of linguistic norm and an outline of forensic linguistics.